Isostructural phase transition (IPT) in CaMoO4 with Scheelite structure. Issue 11 (1st June 2022) - Ramarao, S.D.; Thirmal, C.; Murthy, V.R.K.
Abstract: The ceramic compound CaMoO4 is synthesized via a solid-state reaction technique. Rietveld refinement studies were done on the powder X-ray diffraction data of CaMoO4 and revealed that the compound is crystallized in the tetragonal Scheelite structure with I 41 / a space group. The differential scanning calorimetry (DSC) studies on CaMoO4 divulged an anomaly around 440 °C. This anomaly is further probed using the temperature-dependent Raman and dielectric spectroscopic measurements and are corroborating with the results obtained from DSC. A detailed investigation on the temperature-dependent Raman spectroscopic data revealed that the A1g mode of CaMoO4 showed a soft phonon behavior up to the phase transition temperature. It is observed that the A1g mode displayed phonon hardening behavior with further increasing the temperature. The anomaly is attributed to an isostructural phase transition (IPT), a rarely observed phenomenon in the compounds with Scheelite structure. The IPT in CaMoO4 is elucidated with a phonon softening mechanism.